Contributions to the genus Hetaeria (Orchidaceae: Goodyerinae) in Vietnam - Ponert, Jan (Universidad de Costa Rica, 2014)
As a result of Hon Ba nature reserve survey, Hetaeria finlaysoniana, previously recorded from Thailand, Myanmar and southern China, is newly recorded from Vietnam. Description of studied plants is presented together with notes on ecology and photographic documentation. These plants were collected in southern Vietnam (Hon Ba Nature Reserve, Khanh Hoa), which is located quite far from other known localities and thus a larger distribution of this possibly overlooked species could be expected. Additionally, H. youngsayei is newly recorded from the same reserve, 540 km from the nearest previously known locality. Distribution of both species is discussed and an updated identification key for all Vietnamese members of the genus Hetaeria is presented.